Pre-exercise isomaltulose intake affects carbohydrate oxidation reduction during endurance exercise and maximal power output in the subsequent Wingate test - Naoko Onuma; Daisuke Shindo; Eriko Matsuo; Miki Sakazaki; Yukie Nagai; Kentaro Yamanaka (BMC, 2023)
Abstract Background Ingestion of low-glycemic index (GI) isomaltulose (ISO) not only suppresses subsequent carbohydrate (CHO) oxidation but also inversely retains more CHO after prolonged endurance exercise. Therefore, ISO intake may affect anaerobic power output after prolonged endurance exercise. This study aimed to clarify the time course of CHO utilization during endurance exercise after a single intake of ISO or sucrose (SUC) and the anaerobic power output at the end of endurance exercise. Methods After an intake of either ISO or SUC, 13 athletes were kept at rest for 60 min. Thereafter, they performed a 90-min of treadmill running at their individual target level of % $${\rm{\dot V}}{{\rm{O}}_2}$$ max. During the experimental session, the expired gas was recorded, and the energy expenditure (EE) and CHO oxidation rate were estimated. Immediately after 90 min of running, a 30-s Wingate test was performed, and the maximal anaerobic power output was compared between the ISO and SUC conditions. Results The percentage of CHO-derived EE increased rapidly after CHO intake and then decreased gradually throughout the experiment. The slopes of the regression lines calculated from the time course in the CHO-derived EE were significantly (negatively) larger in the SUC condition (-19.4 ± 9.6 [%/h]) than in the ISO condition (-13.3 ± 7.5 [%/h]). Furthermore, the maximal power output in the Wingate test immediately after the endurance exercise was significantly higher in the ISO condition than in the SUC condition (peak power: 12.0 ± 0.6 vs. 11.5 ± 0.9 [W/kg]). Conclusion Compared with SUC intake, ISO intake does not produce an abrupt decline in the percentage of CHO-derived EE during prolonged endurance exercise; it remains relatively high until the final exercise phase. Additionally, anaerobic power output at the end of the exercise, largely contributed by anaerobic glycolysis, was greater after ISO intake than after SUC intake.